"Don Juan-Fracture" as a Hint to Aortic Isthmus Rupture. (18th November 2014) - Suksompong, Sirilak; von Bormann, Benno
Abstract : We report a case of thoracic aortic rupture after blunt trauma in a 23-year-old male patient. The initial investigation found no external injury or bleeding, only a slightly widened mediastinum and a broken left calcaneus. Abdominal lavage was negative, biochemistry was normal, and breathing and oxygenation were not compromised. When changing his position during diagnostics, the patient all of a sudden developed cardiac arrest and typical signs of hypovolemic shock. An immediate sternotomy was done without any further diagnostics on suspicion of aortic isthmus injury. A circular avulsion at the ligamentum arteriosum was found as assumed and repaired under cardiopulmonary bypass. The patient left the hospital for rehabilitation after 12 days in adequate health status. Biodynamics of blunt trauma after high-speed frontal impact and the relationship between calcaneus fracture, called "Don-Juan fracture, " and aortic rupture at the site of ligamentum arteriosum are discussed.